2019
DOI: 10.1098/rsfs.2018.0084
|View full text |Cite
|
Sign up to set email alerts
|

Glycan-decorated protocells: novel features for rebuilding cellular processes

Abstract: In synthetic biology approaches, lipid vesicles are widely used as protocell models. While many compounds have been encapsulated in vesicles (e.g. DNA, cytoskeleton and enzymes), the incorporation of glycocalyx components in the lipid bilayer has attracted much less attention so far. In recent years, glycoconjugates have been integrated in the membrane of giant unilamellar vesicles (GUVs). These minimal membrane systems have largely contributed to shed light on the molecular mechanisms of cellular processes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 161 publications
(215 reference statements)
1
16
0
Order By: Relevance
“…LecA becomes enriched over time at the interfaces between adjacent cells. This confirms a recently published observation that LecA crosslinks protocells to form prototissues (Villringer et al, 2018;Omidvar and Römer, 2019). One LecA, crosslinking two neighboring cells, might encounter less steric hindrance than binding to up to four Gb 3 on the flat surface of a single cell.…”
Section: Leca Binding Dynamics and Effects On Membrane Topologysupporting
confidence: 91%
“…LecA becomes enriched over time at the interfaces between adjacent cells. This confirms a recently published observation that LecA crosslinks protocells to form prototissues (Villringer et al, 2018;Omidvar and Römer, 2019). One LecA, crosslinking two neighboring cells, might encounter less steric hindrance than binding to up to four Gb 3 on the flat surface of a single cell.…”
Section: Leca Binding Dynamics and Effects On Membrane Topologysupporting
confidence: 91%
“…In addition to recent studies that have shown crosslinking of glyco-decorated vesicles (so-called proto-cells) and the organization of proto-cells into proto-tissues (i.e., the assembly of proto-cells into tissue-like structures) mediated by FS-Janus lectin [39], we aimed to further characterize the potential of the FS-Janus lectin. We used giant unilamellar vesicles (GUVs) (i.e., lipid bilayer spheres with variable sizes up to the dimensions of human cells that can be functionalized with diverse glycans) [41]. We incubated FS-Janus lectin (200 nM) with two populations of GUVs, functionalized with either GM3 (monosialodihexosylganglioside, containing sialic acid) or FSL-A (function-spacer-lipid comprised of the blood group A trisaccharide containing fucose) and monitored the evolving interactions over time.…”
Section: Fs-janus Lectin Induces Lipid Exchange Between Gm3-and Blood Group a Trisaccharide-decorated Guvsmentioning
confidence: 99%
“…The following paragraphs focus on the interactions of lectins with GSLs, which can impose various effects on plasma membrane organization and dynamics (reviewed in [120,121]). In addition to cellular studies, the use of synthetic membrane systems, such as giant unilamellar vesicles or supported lipid bilayers, has contributed substantially to the understanding of the mechanistic details underlying lectin-GSL interactions (reviewed in [122,123]). GSLs are mainly found in the extracellular leaflet of the plasma membrane.…”
Section: Lectin-glycolipid Interactions Induce Membrane Curvature Leading To Tubular Membrane Invaginationsmentioning
confidence: 99%